2019
DOI: 10.1038/s42004-019-0161-0
|View full text |Cite
|
Sign up to set email alerts
|

Extreme multi-valence states in mixed actinide oxides

Abstract: To assure the safety of oxide-fuel based nuclear reactors, the knowledge of the atomic-scale properties of U 1−y M y O 2±x materials is essential. These compounds show complex chemical properties, originating from the fact that actinides and rare earths may occur with different oxidation states. In these mostly ionic materials, aliovalent cationic configurations can induce changes in the oxygen stoichiometry, with dramatic effects on the properties of the fuel. First studies on U 1−y Am y O 2±x indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…The DFT+U approach was used with the help of Quantum Espresso v. In case of Am-doped UO 2 , the situation was found to be different. It was reported that americium introduced into the UO 2 lattice is predominantly in the Am(III) state [111][112][113][114][115][116][117][118]…”
Section: What We Can Know Defect Non-stoichiometry and Doping Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DFT+U approach was used with the help of Quantum Espresso v. In case of Am-doped UO 2 , the situation was found to be different. It was reported that americium introduced into the UO 2 lattice is predominantly in the Am(III) state [111][112][113][114][115][116][117][118]…”
Section: What We Can Know Defect Non-stoichiometry and Doping Effectsmentioning
confidence: 99%
“…using the XAS technique at the U L 3 edge 112 . Although, the possibility of the existence of complex defects in oxygen sublattice upon Am doping was discussed 117 the involvement of oxygen in the charge compensation mechanism in terms of changes in the electronic structure was not analyzed.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…X-ray absorption fine-structure (XAFS) spectroscopy, including (conventional) X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine-structure (EXAFS) spectroscopies, has been since the early 1990s one of the most universal methods to study actinide speciation in liquids, solids and at interfaces, with applications including fundamental, coordination, environmental and materials chemistry of actinides (Nitsche, 1995;Denecke, 2006;Geckeis et al, 2013;Maher et al, 2013;Epifano et al, 2019). In fact, the first version of ROBL built in 1997 was dedicated to XAFS as a sole method to study actinide chemistry (Reich et al, 2000).…”
Section: Xafsmentioning
confidence: 99%
“…[46][47][48][49][50][51] XANES at the metal L and M edges is also used in Ln and An chemistry research. 26,36,[52][53][54][55][56][57][58][59][60][61][62][63][64][65] The L edge probes dipole-allowed 2p → nd transitions and also provides information about the fshell occupation. The (relative) intensity between the spectral features, and the energy of the main edge, are very sensitive to the metal oxidation state and f-electron count.…”
Section: Introductionmentioning
confidence: 99%